Thermodynamic stabilization of crystalline silicon carbide polymer‐derived ceramic fibers - Gerson J. Leonel; Shakir Bin Mujib; Gurpreet Singh; Alexandra Navrotsky (International Journal of Ceramic Engineering & Science, 2022)
Abstract Three crystalline SiC fibers were studied: Tyranno, Hi‐Nicalon, and Sylramic. Thermodynamic stability of the SiC fibers was determined by high temperature oxide melt solution calorimetry. Results shed light on the thermodynamic penalty or benefit associated with microstructural modification of the ceramic fibers, and how energetics correlate to mechanical properties. Enthalpies of formation from components (SiC, SiO2, Si3N4, and C, ∆H°f,comp) for Tyranno, Hi‐Nicalon, and Sylramic are −12.05 ± 8.71, −58.75 ± 6.93, and −71.10 ± 8.71 kJ/mol Si, respectively. The microstructure in Sylramic offers the greatest stabilizing effect, thus resulting in its much more exothermic enthalpy of formation relative to elements and crystalline components. In contrast, the microstructure in Tyranno offers the least stabilization. The thermodynamic stability of the fibers increases with increasing mixed bonding (Si bonded to both C and O). From mechanical testing, Young's moduli of Tyranno, Hi‐Nicalon, and Sylramic are 112, 205, and 215 GPa, respectively. Greater thermodynamic stability is correlated with a higher Young's modulus.